1993
DOI: 10.1136/jmg.30.9.745
|View full text |Cite
|
Sign up to set email alerts
|

Integrated study of 100 patients with Xp21 linked muscular dystrophy using clinical, genetic, immunochemical, and histopathological data. Part 3. Differential diagnosis and prognosis.

Abstract: This report is the third part of a trilogy from a multidisciplinary study which was undertaken to investigate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Analysis shows that in frame deletions in this region can result in great phenotypic variability, and not always in BMD, confirming what is reported in this study. In particular, deletions of exons 2-7, 3, 3-9, 5-13, 6-13, and [10][11][12][13] have been frequently associated with disease courses more severe than expected (table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis shows that in frame deletions in this region can result in great phenotypic variability, and not always in BMD, confirming what is reported in this study. In particular, deletions of exons 2-7, 3, 3-9, 5-13, 6-13, and [10][11][12][13] have been frequently associated with disease courses more severe than expected (table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Deletions were found in 63%, a percentage in accordance with other unselected series of DMD patients. 27 Dystrophin can be shown in the retina by immunohistochemical methods. Transcription of the dystrophin gene involves at least five distinct promoters, each of them driving cell specific dystrophins.28 Different dystrophins are present in the brain, muscle, Purkinje cells, Schwann cells, and glial cells,28 and are transcribed by alternative splicing.…”
Section: ;mentioning
confidence: 99%
“…In Becker muscular dystrophy the amount of dystrophin is normal or near normal, but the protein is often smaller than normal and a segment corresponding to the deletion in the gene is missing.5 New techniques for investigating the dystrophin gene and gene product have shown that dystrophinopathy may be expressed clinically in many different waysfor example, as muscle cramps as the only symptom or high serum creatine kinase (s-CK) as the only evidence of muscle disease. [6][7][8][9] Female carriers of the mutation usually are symptom free, but some have symptoms. In some cases this may be due to a non-random inactivation of the X chromosomes, leading to a predominant expression of the X chromosome that has a mutation in the dystrophin gene.…”
mentioning
confidence: 99%